PENCITRAAN PASANGAN JOKO WIDODO – BASUKI TJAHAJA PURNAMA DALAM IKLAN KAMPANYE VERSI “JAKARTA BARU” (Studi Analisis Semiotik Iklan Televisi) - Irmania Yunita; Ainur Rochmaniah; Nur Maghfirah Aesthetika (Universitas Muhammadiyah Sidoarjo, 2013)
The objective of this study is to analyze the meaning contained in communication symbols in the version of